2015
DOI: 10.7314/apjcp.2015.16.17.7987
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Clinical Aspects for Patients with Chronic Lymphocytic Leukemia in Kermanshah, Iran

Abstract: Chronic lymphocytic leukemia (CLL)is the most common leukemia in adults in Western countries but is relatively rare in Asia. Immune hemolytic anemia, Evan's syndrome, lymphadenopathy, organomegaly and B symptoms are the main complaints of patients in CLL. The present retrospective analysis evaluated a group of 109 patients with CLL over a 9-year period, studying correlations between sex, age and overall survival. The patients were hospitalized in the Clinic of Hematology and Oncology, Kermanshah, Iran, between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 32 publications
(18 reference statements)
5
13
0
1
Order By: Relevance
“…The mean age of our cohort was 63 years, similar to the 56–64 years reported in the literature . It has been estimated that 52–62% of chronic lymphocytic leukaemia (CLL) patients have hypogammaglobulinaemia at diagnosis , with 17–27·3% having IgG deficiency .…”
Section: Discussionsupporting
confidence: 76%
“…The mean age of our cohort was 63 years, similar to the 56–64 years reported in the literature . It has been estimated that 52–62% of chronic lymphocytic leukaemia (CLL) patients have hypogammaglobulinaemia at diagnosis , with 17–27·3% having IgG deficiency .…”
Section: Discussionsupporting
confidence: 76%
“…9 In Iran, Payandeh et al also reported varying rates of organomegaly (34%) and lymphadenopathy (38.7%). 2 The diversity of clinical presentations in CLL and correlations with ethnicity have been well documented in previous research. 13 The incidence of anaemia and AIHA in the current study (78.1% and 11%, respectively) was comparable to that reported in previous research in which AIHA was documented in up to 11% of late-stage CLL patients, with positive DAT results seen in up to 15% of patients.…”
Section: Discussionmentioning
confidence: 77%
“…In the current study, the median age at diagnosis of CLL patients in Erbil, Iraq, was similar to that reported in neighbouring countries such as Iran and Turkey (65 years versus 60.73 and 64 years, respectively). 2,9 In contrast, the median age at diagnosis in Western countries is much higher, ranging from 67-72 years old. 1,10,11 However, the frequency of male CLL patients in the current study was identical to that reported in Italy (64%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations